Genetic structure of Phytophthora infestans sensu lato assessed using microsatellite markers - Hernandez-Diaz, Tharling Yadhannia; Martinez-Palacios, Edison; Salazar-Gonzalez, Claudia Elizabeth; Lagos, Luz Estela (Revista de Ciencias Agrícolas, 2026)
Phytophthora infestans sensu lato is a phytopathogenic oomycete that causes late blight in Solanaceae and has a significant global impact. Its rapid evolution requires population monitoring using polymorphic markers to detect new genotypes with greater biological efficacy. In this context, this study aimed to evaluate the genetic variability of isolates of Phytophthora infestans sensu lato obtained from different species of Solanaceae cultivated in southern Colombia. A total of 40 pathogen isolates were collected from different hosts, including Solanum tuberosum, Solanum lycopersicum, Solanum muricatum, and Solanum betaceum. Genomic DNA was extracted and amplified using 12 microsatellite markers, and the resulting fragments were visualized on 3% agarose gels. Amplification band sizes were measured using ImageJ, and data analysis was performed using the Poppr package in R. High marker polymorphism was observed, with more than four alleles amplified per locus, evidence of triploidy, and high genetic diversity compared to other regions of Colombia. Populations were structured according to their host, with genetic differentiation (Gst) values ranging from 0.24 to 0.65, likely influenced by host preference and the presence of alternative hosts. Linkage disequilibrium analysis suggested asexual reproduction in Phytophthora betacei populations and possible sexual reproduction in P. infestans populations from potato, sweet cucumber, and tomato, emphasizing the need for further investigation of these populations. The markers were highly informative in both the diversity and the reproductive form of the oomycete.